2016
DOI: 10.1128/jvi.02161-15
|View full text |Cite
|
Sign up to set email alerts
|

PACT- and RIG-I-Dependent Activation of Type I Interferon Production by a Defective Interfering RNA Derived from Measles Virus Vaccine

Abstract: The live attenuated measles virus vaccine is highly immunostimulatory. Identification and characterization of its components that activate the innate immune response might provide new strategies and agents for the rational design and development of chemically defined adjuvants. In this study, we report on the activation of type I interferon (IFN) production by a defective interfering (DI) RNA isolated from the Hu-191 vaccine strain of measles virus. We found that the Hu-191 virus induced IFN-␤ much more potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 72 publications
0
47
0
Order By: Relevance
“…RIG-I is triggered by binding of 5′ di-or triphosphates present on uncapped RNA or short regions of double-stranded (ds)RNA. Phosphatase treatment suppresses the ability of in vitro-transcribed copy-back DVGs to trigger IFN production following transfection supporting the role of RIG-I in DVG sensing 91,94,96 . SeV DVGs can also associate with melanoma differentiation-associated protein 5 (MDA5) 88,94 , but the role for MDA5 in sensing other DVGs is less clear 99,100 .…”
Section: Moi Multiplicity Of Infection Ratio Of Infectious Virus Tomentioning
confidence: 79%
See 1 more Smart Citation
“…RIG-I is triggered by binding of 5′ di-or triphosphates present on uncapped RNA or short regions of double-stranded (ds)RNA. Phosphatase treatment suppresses the ability of in vitro-transcribed copy-back DVGs to trigger IFN production following transfection supporting the role of RIG-I in DVG sensing 91,94,96 . SeV DVGs can also associate with melanoma differentiation-associated protein 5 (MDA5) 88,94 , but the role for MDA5 in sensing other DVGs is less clear 99,100 .…”
Section: Moi Multiplicity Of Infection Ratio Of Infectious Virus Tomentioning
confidence: 79%
“…Immunostimulatory DVGs can be recognized by pattern recognition receptors (PRRs), including Toll-like receptors (TLRs) and RIG-I-like receptors (RLRs). While TLR signalling is not essential for production of type I IFNs in vitro in response to DVGs, RLR signalling is required 55,88,[94][95][96][97][98] . SeV copy-back DVGs are stronger immunostimulators than deletion DVGs 89 and are among the strongest known inducers of the antiviral response.…”
Section: Moi Multiplicity Of Infection Ratio Of Infectious Virus Tomentioning
confidence: 99%
“…It has been demonstrated that PACT-dependent activation of IFNβ production was inhibited by all three subunits of IAV polymerase 57,58 . In an RNP reconstitution assay, knocking down PACT in IAV-infected A549 cells enhanced vRNA production and the subsequent IFN response 59 . Of interest, there might be interplay between PACT and other viral molecules, such as the herpes simplex virus type 1 (HSV-1) Us11 protein, Middle East respiratory syndrome coronavirus (MERS-CoV) 4a and the nucleocapsid of the Ebola virus (EBOV) VP35, mouse hepatitis virus (MHV) N proteins and influenza A virus NS1 [60][61][62][63] .…”
Section: Discussionmentioning
confidence: 96%
“…For a wide range of human-pathogenic viruses, such as Ebola virus (EBOV), influenza A virus (IAV), Middle East respiratory syndrome coronavirus (MERS-CoV), human T-cell leukemia virus 1 (HTLV-1), mouse hepatitis virus (MHV), measles virus (MeV), and herpes simplex virus 1 (HSV-1), their viral proteins or defective interfering (DI) RNAs have been shown to modulate the PACT-mediated enhancement of the function of RIG-I to drive the expression of type I IFNs (24,(26)(27)(28)(29)(30)(31)(32). Specifically, the EBOV VP35, IAV NS1, HSV-1 Us11, MERS-CoV 4a and nucleocapsid (N), as well as MHV N proteins have been shown to directly abolish the interaction between RIG-I and PACT and, hence, block the ability of PACT to activate RIG-I (24,(26)(27)(28)(29)32).…”
mentioning
confidence: 99%